Modern multithreading : implementing, testing, and debugging multithreaded Java and C++/Pthreads/Win32 programs - Carver, Richard H., 1960-; Tai, Kuo-Chung.; Wiley InterScience (Online service) (Hoboken, NJ : Wiley, 2006)
Master the essentials of concurrent programming, including testing and debuggingThis textbook examines languages and libraries for multithreaded programming. Readers learn how to create threads in Java and C++, and develop essential concurrent programming and problem-solving skills.
Introduction to concurrent programming -- The critical section problem -- Semaphores and locks -- Monitors -- Message passing -- Message passing in distributed programs -- Testing and debugging concurrent programs.
Includes bibliographical references and index.
Print version record.
Keywords: Parallel programming (Computer science); Threads (Computer programs); Programmation parallèle (Informatique); Threads (Logiciels); COMPUTERS -- Programming -- Open Source; COMPUTERS -- Software Development & Engineering -- Tools; COMPUTERS -- Software Development & Engineering -- General; Parallel programming (Computer science); Threads (Computer programs); FACinfotech -- Computer science; ER -- Internet -- Book -- Full text; Electronic books